2011
DOI: 10.1097/ijg.0b013e3181e079ed
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Macular Thickness and Peripapillary Retinal Nerve Fiber Layer Thickness for Detection of Early Glaucoma Using Spectral Domain Optical Coherence Tomography

Abstract: For the diagnosis of early glaucoma by SD-OCT, macular parameters had high discriminating power and high reproducibility comparable with peripapillary RNFL parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
96
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 20 publications
13
96
2
1
Order By: Relevance
“…This approach does not depend on averaging the thickness of the area ( ¼ thickness divided by area) that has been used in most of the earlier studies for glaucoma detection using OCT. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Calculating the average thickness with this area underestimates the local RGC loss as it takes into account the area with a normal or less affected RGC population. Although this averaging effect would decrease in sector analysis, it would remain present when the area with local RGC loss is smaller than the sectors or across multiple sectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach does not depend on averaging the thickness of the area ( ¼ thickness divided by area) that has been used in most of the earlier studies for glaucoma detection using OCT. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Calculating the average thickness with this area underestimates the local RGC loss as it takes into account the area with a normal or less affected RGC population. Although this averaging effect would decrease in sector analysis, it would remain present when the area with local RGC loss is smaller than the sectors or across multiple sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Regional thickness using predefined sectors, such as the Early Treatment Diabetic Retinopathy Study (ETDRS) and glaucoma sector charts, has been used to detect local macular RGC loss. [14][15][16][17][18][19][20][21] However, the same averaging effects may be present within the sectors, and developing a predefined sector that encloses the entire area with local RGC loss is difficult because areas of RGC loss differ from patient to patient. We explored a new approach for detecting local loss of macular RGCs by using the lowest ganglion cell-inner plexiform layer thickness (GCIPL) among the 360 spokes (termed ''minimum GCIPL'') based on ganglion cell analysis in a macular elliptical annulus developed on a macular cube scan with OCT software (Cirrus HD-OCT; Carl Zeiss Meditec, Inc., Dublin, CA).…”
mentioning
confidence: 99%
“…1 Therefore, a detailed evaluation of neuronal measures in relation to retinal vascular findings will broaden our understanding of this potentially sight-threatening condition. In this regard, optical coherence tomography (OCT) has been demonstrated as a noninvasive, repeatable, and effective technique 2 that can detect subtle neuroretinal degeneration in people with diabetes prior to the appearance of clinical signs of DR. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] OCT is capable of quantifying structural changes at specific retinal layers and is being utilized in the monitoring of therapeutic interventions and in predicting the prognosis of retinal complications in diabetes. In addition to neuoretinal complications, recent studies have documented diabetes-related neural degeneration in the cornea in relation to the presence [17][18][19][20] and severity 21 of peripheral neuropathy, with the help of corneal confocal microscopy (CCM).…”
mentioning
confidence: 99%
“…This has specifically enhanced the measurement of the three main retinal layers associated with glaucomatous damage, namely retinal nerve fiber layer, ganglion cell layer and inner plexiform layer, collectively called the ganglion cell complex (GCC). Previous studies using the time domain OCT have reported the peripapillary RNFL thickness parameters to have superior diagnostic ability than the macular thickness parameters in the diagnosis of early glaucoma [2] . However, many recent studies using the spectral domain (SD-OCT) have shown inconsistent results with better performance of macular parameters in a few of them [4,7] and equal performance [8,9,10] or even better performance of RNFL parameters [5,11] in others.…”
Section: Introductionmentioning
confidence: 99%
“…Ganglion cells (RGCs) and retinal nerve fiber layer (RNFL) constitute 30% to 35% of the macular retinal thickness. In addition, more than half the total number of ganglion cells (RGCs) in the retina are located in the central macula in more than one cell layer thickness [2,3] . Quantification of the changes that occur in the macula has hence been proposed to detect glaucoma in the early stages [3,4] .…”
Section: Introductionmentioning
confidence: 99%